Regional Specialization of Greek Prefectures for the Time Period 1981-2001 - Spyridon Sofios; Garyfallos Arabatzis (European Regional Science Association (ERSA), 2006)
Intense regional inequalities are considered to be widespread in Greece. Indeed, Athens mainly, and Thessaloniki consist the two poles in Greece, Thessaloniki in a lower degree though. In these two cities the larger part of industrial activity, as well as, tertiary sector activities, is assembled. On the contrary, in the other Greek regions not only the economic activities but also the infrastructures have been developed in smaller degree. Moreover, as it is well known, two Greek regions (Northern Aegean, Epirus) are among the poorest in the European Union. This fact constitutes a reluctant factor to the effort of Greece to increase the standard of living of the citizens. In addition, the last two decades, a significant decrease of the contribution of primary sector to the GDP with simultaneous increase of the contribution of the tertiary sector is observed. The particular change involves significant repercussions to the national economy. The aim of this paper is the study of the specialization of Greek prefectures as well as spatial distribution of 13 sectors of economic activity using employment data and methods of regional analysis such as Gini – Hirschman coefficient, Location Quotient Coefficient (LQ), Coefficient of Location (CL), Coefficient of Specialization (CS) and analysis of variation – participation.
Keywords: 330